Strategi Bertahan Hidup Penambang Emas di Desa Bulontio Timur Kecamatan Sumalata Kabupaten Gorontalo Utara - Hatu, Dewinta Rizky R.; Latare, Sainudin; Lapasaw, Mohamad Riski (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
This study aims to analyze the survival strategies implemented by gold miners in Bulontio Timur Village, Sumalata District, North Gorontalo Regency. The research method used is a qualitative approach with a descriptive design. Data were collected through observation techniques, in-depth interviews, and documentation studies. The results of the study indicate that gold miners in Bulontio Timur Village rely on mining as their main source of income because agricultural products are not sufficient for their living needs, especially during the dry season or crop failures. In carrying out mining activities, miners must ask permission from the mine owner known as the